Possible Russian invasion of Ukraine, scenarios for sanctions, and likely economic impact on Russia, Ukraine and the EU - Vasily Astrov; Richard Grieveson; Artem Kochnev; Michael Landesmann; Olga Pindyuk (The Vienna Institute for International Economic Studies (wiiw), 2022)
It remains unclear whether or not Russia will actually invade Ukraine, and if it does so, what form this invasion will take. In this note, we outline two broad scenarios: targeted strikes by Russia in Ukraine accompanied by further non-military destabilisation efforts, or a full invasion, and we analyse the implications of both. In the first scenario, we would expect a more limited sanctions response, particularly from the EU, while a full invasion would entail major sanctions from the West as a whole. Applying a stylized VARX model on Russian quarterly time series, we find no statistically significant impact of sanctions on either Russian GDP or the FX rate. However, we find that Russia is extremely vulnerable to a reduction in the price or volume of its energy exports. This truly nuclear sanctions option-that of restricting energy trade between Russia and the EU -is unlikely given the sizeable negative impact it would have on both sides. Aside from energy, the most painful sanctions would include cutting Russian banks off from the SWIFT system and dollar markets, and bans on exports of high-tech goods to Russia. While Russia has become increasingly insulated from the dollar-based global system, and has built up substantial buffers which it can deploy in the case of sanctions, under the adverse scenario the state would have to make large-scale interventions to maintain economic and financial stability. Under both scenarios, the Ukrainian economy would suffer, and would require major Western support to maintain macro-financial stability. Over the medium run, the current crisis will further isolate Russia economically, leading to a continuation of its very mediocre growth performance since 2014. It will also likely accelerate EU moves towards energy diversification away from Russia. However, the economic impact of this on Russia will be likely mitigated by even closer energy ties between Russia and China.
Keywords: F51; E31; 330; Ukraine; Russia; EU; US; sanctions; energy; CEE